STUDIES REGARDING THE ECONOMICAL APPROACH OF PEAR FRUITS COMMERCIALIZATION ACCORDING TO THE QUALITATIVE ASPECTS - Lenuta CHIRA; Adrian CHIRA; Elena DELIAN; Ligia ION; Constantin NICOLAE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
There are many situations where farmers exploit their fruit production just as it was harvested, without sorting the fruit by their quality or diameter. The present study that was carried out followed an economic approach of the pear fruit exploitation in terms of some quality aspects, namely it has highlighted the advantage of sorting the fruit into quality classes, as opposed to selling the fruit engross after being harvested from the orchard. The pear fruit belonging to the Conference, Beurre Bosc, Orizont and Cristal cultivars originated from a ten year old orchard located in the Bucharest area. The Orizont and Cristal cultivars in comparison with the Conference and Beurre Bosc cultivars display a genetic resistance to pear scab and fire blight diseases, which determined lower production costs, mainly due to less pre harvest intervention applied in the orchard. Both because of the above mentioned fact and the commercialization of the fruit after sorting, the obtained profit was between 1,150 RON/ha for the Conference cultivar and 13,900 RON/ha for the Cristal cultivar. This determined a higher value of profit, respectively between 5.5% and 25.1% in the case of the fruit sorted by quality criteria than for those exploited directly from the orchard, as soon as they have been harvested without any other postharvest intervention.